Curcumin Ameliorates Paclitaxel-Induced Pain Hypersensitivity via Alleviation of Inflammation and Oxidative Stress in Rats: Pharmaceutical Sciences-Pharmacology - Pasupulati, Haritha; SV Padi, Satyanarayana; Koganti, Bharathi; Koganti, Prasad VSRG (International Journal of Life Science and Pharma Research, 2021)
Painful peripheral neuropathy is the main dose-limiting and long lasting side-effect of paclitaxel therapy. Despite enormous research, there is no effective treatment for paclitaxel-induced peripheral neuropathic pain owing to poor understanding of pathophysiological mechanisms. Growing evidence indicates oxidative-nitrosative stress is one of the leading factors causing chemotherapy induced peripheral neuropathy. Recently, involvement of neuroinflammation has been suggested in the development of paclitaxel-induced neuropathic pain. It is postulated that abrogating cytokine release and improving antioxidant defenses might be suitable targets in controlling neuroinflammation and oxidative-nitrosative stress mediated nociceptive hypersensitivities. Therefore, the study evaluated the effect of curcumin on paclitaxel-induced neuropathic pain in rats. Peripheral neuropathy was induced by administration of paclitaxel (2 mg/kg per injection) intraperitoneally on four alternate days (days 0, 2, 4, 6). Thermal hyperalgesia and mechanical allodynia were assessed and the markers of inflammation and oxidative-nitrosative stress were estimated. Administration of curcumin (50 and 100 mg/kg, p.o.) for 2 weeks started 14 days after paclitaxel injection significantly alleviated paclitaxel-induced nociceptive behavioural hypersensitivity observed as reduced thermal hyperalgesia and mechanical allodynia. These observed ameliorative effects of curcumin on paclitaxel-induced neuropathic pain are accompanied by reduction of tumour necrosis factor-α, a pro-inflammatory cytokine, in both spinal cord and dorsal root ganglia and oxidative-nitrosative stress in spinal cord. The results of the present study demonstrated antihyperalgesic and antiallodynic effects of curcumin. Additional clinical studies are warranted to evaluate therapeutic potential of curcumin as antinociceptive agent in the treatment of paclitaxel-induced neuropathic pain.